Weighted Maps: Location-aware Treemaps - Ghoniem, Mohammad; Cornil, Maël; Stefas, Mickaël; Otjacques, Benoît (Poster session of IEEE InfoVis'14, 2014)
The wide availability of quantitative geolocated structured data, e.g. census data, makes it desirable for classic tree visualizations to be location-aware. In this paper, we introduce a new treemap algorithm that produces rectangular cartograms consistently with the known location of data points on a geographic map.